King Henri III’s politique Attack on France’s Catholic Heritage in La Guisiade (1589) - Kanga, Fariba (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2024)
Scholarship on La Guisiade has been keen to emphasize the degree to which Pierre Matthieu’s Henri III recalls representations of the king in contemporary pamphlet literature. Libelles of the 1580s and 1590s commonly defamed Henri III as a lascivious tyrant and sorcerer. However, no scholars to date have noted that Matthieu’s Henri III displays the characteristics of a politique. Although the word politique is only used once in La Guisiade (in the “Argumen” preceding act 4), my contention is that Henri III takes a politique posture towards French politics. He pursues a false peace with the Huguenots and professes an absolutist understanding of sovereignty, privileging his personal will over the will of the people and the Catholic heritage of France. Through the tragic assassination of the Duke of Guise, La Guisiade suggests that politiques are tyrants who work to dismantle France’s heritage and therefore ought not to be trusted.